SISTEM PENDETEKSI WAJAH DENGAN METODE VIOLA JONES MENGGUNAKAN ESP32-CAM - I Made Yudi Candra Putra; I Made Oka Widyantara; I Gusti Agung Komang Diafari Djuni H (Program Studi Teknik Elektro UNUD, 2022)
Increased security in rooms that are confidential or require high privacy, is very muchneeded. One way to increase this security is to use a security system that utilizes the biologicalcharacteristics of facial images that are owned by every human being. The biologicalcharacteristics of human facial images can be a solution for security systems in the roombecause human facial images are difficult to imitate and modify by others. This study aims toimplement a security system for detecting human face images using the Viola Jones methodwith the Haar Classification Feature. The Viola Jones method with the Haar Classificationfeature is suitable as a good visual recognition when detecting facial images via the ESP32-Cam microcontroller and for streaming video using a OV2640 camera. The test results in thisstudy showed that of the 4 objects used in human face images, the ideal distance whendetecting facial images was 30 cm, with a 100% success rate. While the level of slope tolerancethat has been detected is a maximum with a slope of 30° to the position of the face facingstraight ahead.